Farmland value forecasting and the estimation of monthly payment of farmland pension considering the regional differences - Deokho Cho (European Regional Science Association (ERSA), 2015)
The basic concept of a reverse mortgage is loan available to homeowners who are 65 years or older that enables them to convert part of the equity in their home into cash. The loan is called a reverse mortgage because the traditional mortgage payback stream is reversed. Instead of making monthly payments to a lender, as with a traditional mortgage, the lender makes payments to the borrower. You are not required to pay back the loan until the home is sold or otherwise vacated. As long as you live in the home, you are not required to make any monthly payments towards the loan balance, but you must remain current on your property taxes and homeowners insurance. The Korean government adopt the farmland reverse mortgage for the first time in the world, which is called as the Farmland Pension. She has utilized the publicly assessed land value in order to liquidate the farmland equity until now. However, this method is very arguable recently because this assessed value by government is relatively lower than appraisal or transaction values. It means that the monthly payment amount is relatively lower than that by any other farmland value such as the transaction and the monthly appraisal estimation value. This paper uses the monthly dryfield and ricefield data because the pension payment is implemented by the monthly base and to get the more robust estimate values instead of using the quarter or year base data even though the most previous researches used the quarter and year data. It also uses Three Year National Bond as the proxy variable of real interest instead of Company Bond because the transaction of farmland does not occur in real world. The goal of this study tries to figure out the appropriate land value in order to provide the more amount of the monthly payment for the rural elderly who join in the farmland pension system.
Keywords: 330; Farmland Pension; Land; value; forecasting